Adiabatic laminar burning velocities of C3H8-O2-CO2 and C3H8-O2-N2 mixtures at ambient conditions-PART I: Experimental and numerical study. (1st March 2020) - Zhou, Junhu; Liu, Guangyi; Wang, Zhihua; Yang, Weijuan; Liu, Jianzhong; Cen, Kenfa
Highlights: Laminar burning velocities of C3 H8 -O2 -N2 and C3 H8 -O2 -CO2 mixtures at ambient conditions was measured using heat flux method. Five detailed mechanism models were examined in prediction of laminar burning velocities of C3 H8 -O2 -N2 and C3 H8 -O2 -CO2 mixtures at ambient conditions. A correlation between laminar burning velocities and dilution ratio is proposed and validated. Abstract: This study and its companion paper presents a comprehensive study of laminar premixed flames of propane under oxy-fuel and oxygen-enrichment conditions for the first time. Laminar burning velocities were measured with the heat flux method at ambient conditions within an equivalence ratio of 0.6–1.6. The experimental results are discussed by comparison with modeling results from five detailed kinetic mechanisms. All models predicts the correct tendency of laminar burning velocities varies with equivalence ratios but only the UDEL model predicts the accurate laminar burning velocities under O2 -CO2 atmosphere. The laminar burning velocities of C3 H8 -air and C3 H8 + 0.3O2 + 0.7CO2 were selected as reference values SL0, a new correlation S L / S L 0 = ( 1 + α Y enr + β Y enr 2 ) was obtained from the simulations and validated with experiment results. Good agreement between the correlation predictions and experimental results indicating that it is useful to predict SL in the range of this work. Part II will discuss the global flame parameters and the mechanisms of dilution, thermal and chemical effects of diluents on the laminar burning velocities.